The inevitability of digital transfer How prepared are UK public bodies for the transfer of born-digital records to the archives? - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2019)
Purpose This paper aims to assess how prepared public bodies are for the transfer of born-digital records to the National Archives (TNA) of the UK in line with the reduction in the transfer rule from 30 to 20 years. Design/methodology/approach The change in the transfer rule means that records of UK public bodies will be transferred to TNA for permanent preservation at 20 years as opposed to 30 years old. This move, which has been described as a major change that is going to be introduced in a manageable and affordable way (20-year rule, The National Archives), will inevitably witness the transfer of born-digital records to the archives much earlier than would have been the case if the change in the transfer rule had not been made. This paper reports on research carried out in the winter of 2017 on the extent to which UK public bodies are prepared for the transfer of born-digital records to TNA. Research was based on a survey of 23 public bodies which included ministries, charities and non-departmental public bodies. The target population was predominantly public bodies that had the highest level of transfer of records to TNA. The justification for this lies in the fact that these bodies, amongst others, transfer the most records to TNA, thus it would be interesting to gain an insight into how prepared these relatively larger public bodies are with regard to born-digital transfer. The remaining public bodies were chosen randomly amongst non-ministerial departments. The primary areas under analysis are plans of public bodies for the transfer of born-digital records, processes for transfer to be undertaken such as selection, appraisal etc., the use of technology in sensitivity review and the trigger date for the transfer of records. Findings An analysis of the research findings found that while a few UK public bodies surveyed had transferred datasets within the framework of the TNA Government Datasets (NDAD) initiative or as part of an inquiry, only one public body had transferred other born-digital records to TNA. The findings also reveal that most public bodies are yet to plan for, or to adjust, their current archival processes to take into account the different mind-set and skills required for the transfer of born-digital records. The level of preparedness is therefore limited primarily because public bodies have yet to undertake a transfer of born-digital records to the archives. The research findings also revealed that public bodies had not as yet made adjustments or changes to current practice to take into account the issues relating to the processing of born-digital records prior to transfer. Research limitations/implications -The findings of the research at hand are based on a survey submitted electronically to twenty-three public bodies with the aim of assessing how prepared they are for the transfer of born-digital records to the National Archives (TNA). The survey was sent to 27 public bodies with responses received by 23 public bodies. The survey sent to these bodies comprises eight questions that were deemed to be important in the current digital landscape with regard to the processes involved in the transfer of records, beginning from their creation. Thus, an element of subjectivity exists with regard to the outcome of the research, as the public bodies chosen were guided in prioritising any issues about digital transfer through the questions posed. The research carried out is also limited in that it focuses primarily on ministerial departments (14 of the 23 surveyed) and also constitutes a very small sample of UK public bodies overall. However, the originality of the data obtained through the study carried out by far outweighs the limitations of the research methodology. Originality/value -This paper highlights that the transfer of born-digital records through original research amongst the 23 public bodies surveyed is not widespread, and that processes and procedures specifically for the management of processes for born-digital records are yet to be implemented. The study concludes that long-term planning for the transfer of born-digital records is yet to be undertaken and that public bodies are more likely to deal with the issue when their digital records are closer to reaching the point of transfer.
Keywords: Records management; Born-digital records; Digital transfer